КОНЦЕПЦИЯ НЕФТЕГАЗОВЫХ ГЕНЕРАЦИОННО-АККУМУЛЯЦИОННЫХ СИСТЕМ КАК ИНТЕГРИРУЮЩЕЕ НАЧАЛО В ОБОСНОВАНИИ ПОИСКОВО-РАЗВЕДОЧНЫХ РАБОТ - Лопатин Н.В. (My University, 2006)
Described are basic components of petroleum systems: source rocks, which included identification, the mapping pod of active source rocks migration-drainage space, hydrocarbon accumulation processes and preservation time, and two main processes "generation-migration-accumulation of oil and gas, and formation of traps." Also studied is the geographic, stratigraphic and time extension of petroleum systems. It is concluded that application of the petroleum system concept reduces the exploration risk and provides the effective choice of plays and prospects.
Keywords: 553.98:551.8.022.4